Implementasi Pendidikan Karakter Siswa dalam Pembentukan Kepribadian Yang Berakhlak Mulia di Sekolah SMP IT Nurul Fadillah - Farida Khairani Siregar (AR-RASYID : Jurnal Pendidikan Agama Islam, 2021)
The purpose of this study is to understand the implementation of student character education in the formation of noble character in the IT Nurul Fadhillah junior High School. The method used is qualitative research. The research was conducted at the IT Nurul Fadhillah Middle School. The data were obtained from the results of interviews, observations (observations) conducted with the principal of SMP IT Nurul Fadhillah. Based on the data obtained, it can be seen that in instilling character in students, it is done by habituation through various activitities. 1) routine activities carried out by students continuously and consistently at all times 2) activities carried oud by students at a predetermined time 3) exemplary is the behavior, attitude of teachers, education staff and students in setting an example through good actions so that it is expected to be a role model for other students 4) conditioning by creating conditions that support the implementation of student character education in the formation og noble personalities